GROWTH RESPONSE OF ONE YEAR OLD POST PLANTED Shorea leprosula SEEDLING TO VARIOUS LIGHT, UNDER 19 YEARS OLD Acacia mangium STAND - Riyanto, Heru Dwi (Indonesian Journal of Forestry Research, 2006)
Development of  meranti (S.leprosula) plantation forest is limited/ constrained by many factors, e.g.   seed supply and seedling growth environment. The research deals  with the observation of  the current condition on A.  mangium  stand and did not  employ any treatments.  Meranti seedling was obtained from vegetative cutting (Komatsu-Forda), at one year (old) post planted meranti under A. mangium stands  and spacing of 4 x 2 m, approximately two hectares of permanent  sample plot (PSP) were made. Ineach hectare  of young meranti plants with spacing 10  x 3 m  (330 seedling/ha),  9 (nine) observation plots  with size 10 x 10 m (6 seedlings/plot)  were prepared,  and placed in the middle of PSP. Totally, there were 108 seedlings available for the measurement of particular parameter, i.e. light intensity, height growth, and survival rate. Light intensity  was  measured by going around of 10 x 10 m plot.Result of measurement in each observation plot (10 x 10 m size) rescaled that light intensity ranged about  6,55  - 35,2% or being equal with 4908 - 26568 flux hour. Meanwhile, the best height growth response and survivalrate were at 10 %   light intensity or over.